Bioformulation of Bacillus proteolyticus MITWPUB1 and its biosurfactant to control the growth of phytopathogen Sclerotium rolfsii for the crop Brassica juncea var local, as a sustainable approach - Mukadam, Humaira; Gaikwad, Shikha V.; Kutty, Nithya N.; Gaikwad, Vikrant D. (Frontiers in Bioengineering and Biotechnology, 2024)
Bacillus proteolyticus MITWPUB1 is a potential producer of biosurfactant. The organism is also found to be a producer of plant growth promoting (PGP) traits such as hydrogen cyanide (HCN), indole acetic acid (IAA) and solubilizer of phosphate. The biosurfactant was reported to have a blend of two classes of biosurfactants (BS) such as glycolipids and lipopeptides by Thin Layer Chromatography (TLC) and Fourier Transmission Infrared Spectroscopy (FTIR) analysis. Further semi targeted metabolite profiling via LC-MS revealed presence of phospholipids, lipopeptides, polyamines, IAA derivative and carotenoid. The biosurfactant showed dose-dependent antagonistic activity against Sclerotium rolfsii. Investigating the effect of biosurfactant on S. rolfsii by scanning electron microscopy, mycelial deformations and reduction in branching pattern were noticed. In vitro studies, B. proteolyticus MITWPUB1 and its biosurfactant when applied to seeds of B. juncea var local, seed germination rate was enhanced. On the other hand, sawdust carrier based bioformulation with B. proteolyticus MITWPUB1 and its BS showed an increase in growth parameters of B. juncea var L. The study highlights a unique bioformulation combination to control growth of phytopathogen S. rolfsii and as a plant growth enhancer for B. juncea var L. For the first time, Bacillus proteolyticus MITWPUB1 was found to be a prominent biosurfactant producer that has an ability to control the growth of phytopathogen S. rolfsii.